Designing a Christian Religious Education Curriculum for Cambridge-Based SPK Primary Schools in Indonesia for Generation Alpha Learners in the Digital Age - Liuw Tjhin Dji Cung (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
The rapid advancement of digital technologies, widespread access to internet-connected devices, and the increasing presence of artificial intelligence have reshaped children’s learning experiences. In Indonesia, Satuan Pendidikan Kerja Sama schools adopting the Cambridge Primary Curriculum face challenges in integrating Christian Religious Education pedagogically and theologically while responding to the digital realities of Generation Alpha learners. As the first generation fully immersed in digitally mediated environments, these learners require faith education that connects biblical learning with digital literacy, ethical discernment, and responsible technology use. This study designs a Christian Religious Education curriculum model for Cambridge-based Satuan Pendidikan Kerja Sama primary schools in Indonesia aligned with Permendikbud Number 31 of 2014, Cambridge curriculum principles, and the developmental characteristics of Generation Alpha learners. Using a qualitative design-based research approach, the study integrates policy analysis, recent academic literature, and curriculum alignment principles to develop a coherent framework. The proposed curriculum integrates biblical literacy, Christian character formation, digital citizenship, and age-appropriate ethical reflection on artificial intelligence through inquiry-oriented pedagogy and authentic assessment. The model offers a policy-aligned, developmentally appropriate, and digitally responsive approach to faith formation in international school contexts.